Production and verification of novel Osmanthus hybrids - Alexander, Lisa; Wu, Xingbo; Gouker, Fred (Frontiers in Horticulture, 2024)
Osmanthus fragrans Lour. is prized for its fragrant, cool-season blooms, smooth leaves, and compact tree form; however, the species is limited in production and use to USDA Hardiness Zones 7 and higher. Increasing the total amount of genetic variability available for evaluation, selection, and breeding is foundational to the development of novel Osmanthus cultivars with increased cold-hardiness and improved ornamental characteristics such as high rooting rates, faster growth, fragrant flowers, and an evergreen or semi-evergreen habit. Hybridization among Osmanthus species should generate novel phenotypes and allow trait introgression among populations and breeding lines. The objectives of this study were to produce, verify, and evaluate Osmanthus hybrids by making controlled and open-pollinated crosses among Osmanthus species, using SSR markers to determine parentage of cross progeny, and comparing flowering, leaf shape, and form of hybrids offspring with parents. Fifty-eight of 66 progenies (88%) were assigned paternity at the 95% confidence level or above and 47 progenies (71%) were assigned paternity at the 99% confidence level. Novel Osmanthus hybrids were produced including O. armatus × O. fortunei, O. armatus × O. heterophyllus, and O. armatus × O. fragrans. Openpollinated families increased in height an average of 204% and 159% per year in the first and second growing seasons, respectively. Male flower type was significantly associated with progeny flower type (χ 2 = 17.5, p < 0.0001) while leaf margin was not associated with cross family (χ 2 = 0.83, p = 0.84). Evaluation of more Osmanthus accessions and subsequent hybridizations will be necessary to introgress favorable genes and generate the variation necessary to expand the genus into new markets.